Gene Regulatory Pathways Driving Central Nervous System Regeneration in Zebrafish - (:unkn) unknown (My University, 2014)
Damage to the central nervous system (CNS) circuitry of adult mammals results in permanent disability. In contrast, the ability to regenerate damaged CNS nerves and achieve functional recovery occurs naturally in fish. The ability of fish to successfully regrow damaged CNS nerves is in part a consequence of their ability to re-express key neuronal growth-associated genes/proteins in response to CNS injury. On such protein is Growth-Associated Protein-43 (Gap43), a protein which is highly enriched in axonal growth cones during CNS development and regeneration. Experiments conducted in mammals have demonstrated that ectopic expression of GAP-43 improves axonal re-growth after injury. Using zebrafish optic nerve as a model for successful CNS regeneration, we have identified that re-expression of the gap43 gene is crucial for regenerative axon growth in vivo. Using a combination of in vivo reporter assays and in vivo regeneration assays, we also identified transcriptional regulatory pathways that are essential for gap43 gene expression in regenerating CNS neurons. We found that transcription factors Ascl1a, Atf3, cJun and Stat3 are required for both re-initiating gap43 expression and driving axon outgrowth in response to optic nerve injury. Futhermore, our results indicate that transcription factors Ascl1a, Atf3 and cJun function cooperatively to re-initiate gap43 expression in a manner that is conserved across highly divergent teleost species. Together, these experiments provide insights into regulatory mechanisms driving successful CNS regeneration, thereby revealing potential targets that may be manipulated to improve regenerative ability in mammals.
Keywords: Cns Regeneration; Transcription Factors; Zebrafish